PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KPKM (KOPERASI PRODUSEN KOPI MARGAMULYA) DI KECAMATAN PANGALENGAN - Oktavia, Soverani; Karyani, Tuti (Jurnal AGRISEP, 2017)
Cooperative is a business entity that based on kinship and provides services to its members. Service quality of a cooperative affects the members' satisfaction. The existence of service quality is one of the reasons for members to join and contribute to cooperative. KPKM (Cooperative Producer of Coffee Margamulya) as one of the producer cooperative in Bandung Regency provides services to its member who were coffee producers in Margamulya Village. The purpose of this researched (1) to analyze the influence of KPKM service quality toward its member satisfaction (2) to analyze the influence of each service quality dimension to satisfaction of KPKM members. This research uses quantitative method by using multiple linear regression analysis. The result of analysis shows that there was positive influence between service quality of the cooperative and satisfaction of the members. Members' satisfaction can be explained by the service quality as much as 74.9 percent. Based on each quality dimension, the satisfaction of the members was not influenced by the dimensions of responsiveness.